Single-molecule magnetic tweezers to probe the equilibrium dynamics of individual proteins at physiologically-relevant forces and timescales - Tapia-Rojo, Rafael (Nat Protoc, 2024)
The reversible unfolding and refolding of proteins is a regulatory mechanism of tissue elasticity and signalling, used by cells to sense and adapt to extracellular and intracellular mechanical forces. However, most of these proteins exhibit low mechanical stability, posing technical challenges to the characterization of their conformational dynamics under force. Here, we detail the step-by-step instructions for conducting single protein nanomechanical experiments using ultra-stable magnetic tweezers, which enable the measurement of the equilibrium conformational dynamics of single proteins under physiologically-relevant low forces applied over biologically-relevant timescales. We report the basic principles determining the functioning of the magnetic tweezer instrument, review the protein design strategy and the fluid chamber preparation and detail the procedure to acquire and analyze the unfolding and refolding trajectories of individual proteins under force. This technique adds to the toolbox of single-molecule nanomechanical techniques and will be of particular interest to those interested in proteins involved in mechanosensing and mechanotransduction. The procedure takes 4 days to complete, plus 6 additional days for protein cloning and production, requiring basic expertise in molecular biology, surface chemistry and data analysis.